Primary endobronchial multifocal Ewing’s sarcoma: a rare case report - Liu, Dan; Liu, Xiaoge; Li, Xin; Liu, Yisha; Yu, Junlun (Frontiers in Oncology, 2024)
Extraskeletal Ewing's sarcoma (ES) has been reported to originate from various sites. Primary endobronchial ES is an extremely rare bronchial tumor, especially multifocal lesions.This report describes a rare presentation of primary bronchial ES in a 31-year-old female who was referred to the emergency department of our hospital due to suspicion of a foreign body in the bronchus. Computed tomography and bronchoscopy revealed multiple polypoid nodules in the middle bronchus of her right lung, thus excluding the initial diagnosis. Infection-related laboratory tests and serum tumor markers were normal. The bronchial sleeve resection was performed to remove the tumor completely and the patient's clinical symptoms obviously improved. Subsequent imaging, histopathological, immunohistochemical and genetic analyses made a conclusive diagnosis of primary endobronchial ES. To our knowledge, this is the eighth case of primary bronchial ES reported in medical literature.